Effect of Phenolic and Alkaloid Extract of Senna Occidentalis Leaf on the Oxidative Status of the Heart in High Fat-Diet Streptozotocin-Induced Type 2 Diabetic Wistar Rats - Emmanuel Saviour Saheed; Mutiat A. Abdulkareem; Fehintoluwa Celestina Adeleke (World Journal of Traditional Chinese Medicine, 2025)
Objective: This research examined the effects of extracts (alkaloid and phenolic) from the leaves of Senna occidentalis on the oxidative status of heart in Wistar rats fed high-fat diets and induced with streptozotocin. Type 2 diabetes was established in the rats by injecting 35 mg/kg of streptozotocin intraperitoneally. Materials and Methods: Forty-three experimental rats were randomly categorized into seven groups of six rats each, with Group 1 as control group, which comprised seven rats. The remaining groups were as follows: group 2 (untreated diabetic rats), Group 3 (metformin-treated diabetic rats), Group 4 (phenolic extract-treated diabetic rats), Group 5 (alkaloids extract-treated diabetic rats), Group 6 (high-dose phenolic extract-treated diabetic rats), and Group 7 (high-dose alkaloids extract-treated diabetic rats). Results: The activity levels of various biochemical factors such as catalase, superoxide dismutase, glutathione-S-transferase, glutathione peroxidase, glutathione, and malondialdehyde were assessed to determine antioxidant status. Conclusions: The findings of this study demonstrated that the phenolic and alkaloid extracts from S. occidentalis possess antioxidant properties and show promise in the management of type 2 diabetes.